The Structuring of Local Government Organizations: The Perspective of Henry Mintzberg’s Theory - Anam, Khoirul; Bahtiar, Bahtiar (Universitas Muhammadiyah Jember Press, 2025)
The objective of this research is to describe the structure of Village Government Organizations. The focus is to analyze the organizational structuring policy of the Department of Community and Village Empowerment (Dinas Pemberdayaan Masyarakat dan Desa) of Jember Regency. This study employs a qualitative descriptive approach, with sampling determined through snowball sampling. The initial key informants selected were the Head of the Department, the Secretary, and the Head of Division. Data collection techniques included interviews, observation, and documentation, utilizing both primary and secondary data. The study refers to Henry Mintzberg’s (1993) theory of the five structures in designing effective organizations. The findings reveal that the organizational structuring of local government agencies, when examined through Mintzberg’s theory, is less than optimal. First, in the drafting of Regent Regulation No. 44 of 2016 concerning the Position, Organizational Structure, Duties, Functions, and Work Procedures of the Department of Community and Village Empowerment of Jember Regency, there was no local regulation providing technical guidelines for the formulation of regent regulations. Second, the regulation has not substantively fulfilled the principles of rational, proportional, effective, and efficient structuring of local government organizations as outlined by Mintzberg’s theory. This has led to issues such as limited capacity to interpret and operate existing rules. Improvements are required in areas such as the availability of competent and professional human resources, regulatory clarity, effective working relationships, and minimizing political influence in decision-making processes.